Expression and Role of Gonadotropin-Releasing Hormone 2 and Its Receptor in Mammals - Desaulniers, Amy T.; Cederberg, Rebecca A.; Lents, Clay A.; White, Brett R. (Frontiers in Endocrinology, 2017)
Gonadotropin-releasing hormone (GnRH1) and its receptor (GnRHR1) drive mammalian reproduction via regulation of the gonadotropins. Yet, a second form of GnRH (GnRH2) and its receptor (GnRHR2) also exist in mammals. GnRH2 has been completely conserved throughout 500 million years of evolution, signifying high selection pressure and a critical biological role. However, the GnRH2 gene is absent (e.g., rat) or inactivated (e.g., cow, sheep) in some species but retained in others (e.g., human, horse, pig). Likewise, many species (e.g., human, chimpanzee, cow, sheep) retain the GnRHR2 gene but lack the appropriate coding sequence to produce a full-length protein due to gene coding errors; although, production of GnRHR2 in humans remains controversial. Certain mammals lack the GnRHR2 gene (e.g., mouse) or most exons entirely (e.g., rat). In contrast, old world monkeys, musk shrews and pigs maintain the coding sequence required to produce a functional GnRHR2. Like GnRHR1, GnRHR2 is a 7-transmembrane, G-protein coupled receptor which interacts with Gαq/11 to mediate cell signaling. However, GnRHR2 retains an intracytoplasmic tail and is only 40% homologous to GnRHR1. A role for GnRH2 and its receptor in mammals has been elusive, likely because common laboratory models lack both the ligand and receptor. Uniquely, both GnRH2 and GnRHR2 are ubiquitously expressed; transcript levels are abundant in peripheral tissues and scarcely found in regions of the brain associated with gonadotropin secretion, suggesting a divergent role from GnRH1/GnRHR1. Indeed, GnRH2 and its receptor are not physiological modulators of gonadotropin secretion in mammals. Instead, GnRH2 and GnRHR2 coordinate the interaction between nutritional status and sexual behavior in the female brain. Within peripheral tissues, GnRH2 and its receptor are novel regulators of reproductive organs. GnRH2 and GnRHR2 directly stimulate steroidogenesis within the porcine testis. In the female, GnRH2 and its receptor may help mediate placenta function, implantation and ovarian steroidogenesis. Furthermore, both the GnRH2 and GnRHR2 genes are expressed in human reproductive tumors and represent emerging targets for cancer treatment. Thus, GnRH2 and GnRHR2 have diverse functions in mammals which remain largely unexplored.